Ubiquitination in Health and Diseases - Ishigami, Tomoaki (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Ubiquitination is a biological process mediated by ubiquitin itself, the E1 ubiquitin-activating enzyme, E2 ubiquitin-conjugating enzyme, E3 ubiquitin ligase, and deubiquitinating enzyme, respectively. Currently, these multiple biological steps are revealed to participate in various life phenomena, such as cell proliferation, regulation of cell surface proteins expression, and mitochondrial function, which are profoundly related to human health and diseases. Although clinical applications targeting ubiquitination are still limited compared to those directed toward kinase systems such as tyrosine kinases, multiple enzymatic consequences should be future therapeutic implications. This Special Issue of IJMS entitled "Ubiquitination in Health and Disease" successfully published15 distinguished manuscripts, with a total of 66 international authors and. This book provides the latest and most useful information for researchers and scientists in this field.